Town-Gown Conflict. - Ruf, Beatrix; McKenzie, Lucy; Dangleterre, Constance Barrère; McEachan, lucy; Pontégnie, Anne; York, Peter; Duffy, Catriona; Kimpe, Kris (Zürich : JRP/ Ringier, 2011)
Dengler, Verena ; Desamory, Lucile ; Keogh, Caitlin ; pelican avenue ; Lipscombe, Bea ; Radcliff, Elisabeth
Town-Gown Conflict, Kunsthalle Zürich, Zürich, 13 juni tot 14 augustus 2011
boek